Improved electrochemical properties of morphology-controlled titania/titanate nanostructures prepared by in-situ hydrothermal surface modification of self-source Ti substrate for high-performance supercapacitors - Banerjee, Arghya Narayan; Veettikkunnu Chandran, Anitha; Joo, Sang W. (Nature Publishing Group, 2017)
Ti substrate surface is modified into two-dimensional (2D) TiO2 nanoplatelet or one-dimensional (1D) nanorod/nanofiber (or a mixture of both) structure in a controlled manner via a simple KOH-based hydrothermal technique. Depending on the KOH concentration, different types of TiO2 nanostructures (2D platelets, 1D nanorods/nanofibers and a 2D + 1D mixed sample) are fabricated directly onto the Ti substrate surface. The novelty of this technique is the in-situ modification of the self-source Ti surface into titania nanostructures, and its direct use as the electrochemical microelectrode without any modifications. This leads to considerable improvement in the interfacial properties between metallic Ti and semiconducting TiO2. Since interfacial states/defects have profound effect on charge transport properties of electronic/electrochemical devices, therefore this near-defect-free interfacial property of Ti-TiO2 microelectrode has shown high supercapacitive performances for superior charge-storage devices. Additionally, by hydrothermally tuning the morphology of titania nanostructures, the electrochemical properties of the electrodes are also tuned. A Ti-TiO2 electrode comprising of a mixture of 2D-platelet + 1D-nanorod structure reveals very high specific capacitance values (similar to 7.4 mF.cm(-2)) due to the unique mixed morphology which manifests higher active sites (hence, higher utilization of the active materials) in terms of greater roughness at the 2D-platelet structures and higher surface-to-volume-ratio in the 1D-nanorod structures.
Vylepšené elektrochemické vlastnosti morfologicky kontrolovaných titan/titaničitých nanostruktur připravených in-situ hydrotermální modifikací povrchu Ti substrátu pro vysokovýkonové superkondenzátory
Keywords: sensitized solar-cells; titania nanotube array; carbon nanotube; asymmetric supercapacitors; oxide nanoparticles; energy-storage; graphene oxide; double-layer; electrode; capacitance; zcitlivěné solární články; nanotyčinkové pole oxidu titaničitého; asymetrické superkapacitátory; oxidové nanočástice; ukládání energie; oxid grafenu; dvojvrstva; elektroda; kapacitance